2005
DOI: 10.1080/02687030544000227
|View full text |Cite
|
Sign up to set email alerts
|

Treating agrammatic aphasia within a linguistic framework: Treatment of Underlying Forms

Abstract: Background-Formal linguistic properties of sentences-both lexical, i.e., argument structure, and syntactic, i.e., movement-as well as what is known about normal and disordered sentence processing and production, were considered in the development of Treatment of Underlying Forms (TUF), a linguistic approach to treatment of sentence deficits in patients with agrammatic aphasia. TUF is focused on complex, non-canonical sentence structures and operates on the premise that training underlying, abstract, properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 43 publications
5
102
0
4
Order By: Relevance
“…In particular, as noted in the introduction, studies of the TUF approach (Ballard & Thompson, 1999;Jacobs & Thompson, 2000;Thompson & Shapiro, 2005;Thompson et al, 1993Thompson et al, , 1996Thompson et al, , 1997 frequently observed greater generalization to sentences with the same type of movement than to sentences with a different type of movement. Furthermore, it is important to highlight that the focus of the treatments in the current study was on the identification of thematic role in comprehension, which addresses movement only implicitly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, as noted in the introduction, studies of the TUF approach (Ballard & Thompson, 1999;Jacobs & Thompson, 2000;Thompson & Shapiro, 2005;Thompson et al, 1993Thompson et al, , 1996Thompson et al, , 1997 frequently observed greater generalization to sentences with the same type of movement than to sentences with a different type of movement. Furthermore, it is important to highlight that the focus of the treatments in the current study was on the identification of thematic role in comprehension, which addresses movement only implicitly.…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of TUF is to promote generalization from trained to untrained sentences; therefore, researchers systematically probe progress on syntactically related and unrelated untrained sentence structures. It has been found that generalization following TUF is greatest to linguistically related sentences (Ballard & Thompson, 1999;Jacobs & Thompson, 2000;Thompson & Shapiro, 2005;Thompson, Shapiro, & Roberts, 1993;Thompson, Shapiro, Tait, Jacobs, & Schneider, 1996;Thompson et al, 1997), lending support for specific deficit hypotheses that suggest that specific syntactic operations lie at the root of deficits. Furthermore, generalization occurs frequently from complex to simple structures but less frequently from simple to complex structures (Thompson, Ballard, & Shapiro, 1998;Thompson & Shapiro, 2005Thompson, Shapiro, Kiran, & Sobecks, 2003;Thompson et al, 1993Thompson et al, , 1997.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Más recientemente los estudios sobre el tratamiento de la afasia han estudiado los efectos de intervenciones específicas para ciertos défi-cits del lenguaje; de manera tal que sus diseños han involucrado comparaciones intra e intergrupo y diseños experimentales controlados (12,13,14,15,16).…”
Section: Introductionunclassified